(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2023)
The military actions, the loss of human lives and especially the cruelty of the Nazi and Fascist regimes and armies caused a reaction among the allied governments, the public and intellectuals. The Nazi regime in Germany and its actions, in general, even before the beginning of WWII caused an initially mild and later a sharp reaction and criticism in the democratic world. However, the behaviour and fanaticism of the German armed forces and their atrocities during the war could not but cause reflections about how the allied countries, especially the larger ones, should deal with the defeated Germany. The experience of WWI had shown that German Nazism had, as its basis, the militarism which was present everywhere, including in the educational process. That is why many in the United States and Great Britain began to think aloud about a complete change of the German educational system and the re-education of the Germans after the military victory. There was a great dilemma over the questions of how to carry out that re-education, whether to include only the younger population that was exposed to Nazi indoctrination, and whether Germans who were opponents of Nazism should be included in that process. The debates were conducted among politicians, in the public, among scholars and scientists. The view that gradually prevailed was that the issue was complex and that some Germans should be involved in the re-education process after the War.